Autonomy and competence frustration in young adolescent classrooms: Different associations with active and passive disengagement. (June 2017) - Earl, Stephen R.; Taylor, Ian M.; Meijen, Carla; Passfield, Louis
Abstract: Few studies have attempted to identify distinct psychological correlates of different forms of classroom disengagement. Drawing from basic psychological needs theory (Deci & Ryan, 2000), this study investigated two divergent mechanisms predicting active and passive classroom disengagement. Pupils ( N = 647; age = 11–14 years) and their respective teachers completed a questionnaire measuring the study variables. Using structural equation modelling, pupils' perceptions of teacher psychological control positively predicted pupils' autonomy and competence frustration in class. Pupils' competence frustration indirectly and positively associated with teacher-rated passive disengagement (e.g. daydreaming in class), via reduced feelings of vitality. Pupils' autonomy frustration demonstrated positive associations with both active disengagement (e.g. talking and making noise) and passive disengagement but neither relationship was explained by feelings of vitality. These distinct mechanisms may have implications for educators, identifying potential causes of different forms of pupil disengagement and the importance of avoiding psychological control in classrooms. Highlights: We investigated processes predicting active and passive disengagement in classrooms. Teacher psychological control predicted pupils' autonomy and competence frustration. Competence frustration indirectly predicted passive disengagement via reduced vitality. Autonomy frustration directly predicted active and passive disengagement but not via vitality.